The hidden crisis: double burden of malnutrition among refugee children in South Asia – a systematic review and meta-analysis from observational studies - Panchal, Pooja; Usman, Mohd; Longkumer, Tajung; Babu, Reshma Susan; Khatib, Mahalaqua Nazil; Razak, Shariza Abdul; Menon, Kavitha (Frontiers in Nutrition, 2025)
Background: Children living in refugee camps in South Asian countries suffer from undernutrition. However, the emerging prevalence of double burden of malnutrition could cause a crisis in the healthcare of the refugee population. The study aims to assess the prevalence of malnutrition among refugee children in South Asia. Methods: This systematic review and meta-analysis followed the standard PRISMA 2020 guidelines using CoCoPop mnemonic approach. We searched JSTOR, Scopus, PubMed, Web of Science, and MEDLINE databases for studies on prevalence of malnutrition in refugee children from 1984 to August 2024 with restricted English language. The screening of research articles was undertaken using COVIDENCE 2.0 software. JBI checklist was used to assess the methodological quality of the included articles. The pooled prevalence was estimated using Med Calc software. The grey literature was manually searched from the reputed organizations focusing on refugee children and was narratively analyzed for malnutrition statistics. Furthermore, primary research articles and grey literature were corroborated to provide a comprehensive understanding. The review included ten full-text research articles, all with cross-sectional study designs, and 11 grey literature. The ten studies covered a total of 4274 participants with 3536 urban and 738 rural refugee children aged between 0-19 years (refugee children (n=8) and refugee adolescents (n=2)). The sample size of the included studies varied between 58-1087 and mostly from Bangladesh. The prevalence of stunting ranged from 3.9%-75.4% in the included studies (pooled prevalence: 31.8% (95% CI: 18.6%-46.6%)); wasting between 0.3%-24.3% (pooled prevalence:10.1% (95% CI: 4.6-17.3)); underweight between 4.4%-65% (pooled prevalence: 19.1% (95% CI: 10.8%-29.2%)); and overweight between 3%-24% (pooled prevalence: 6.5% (95% CI: 2.6%-12.1%). Time trend analysis of the prevalence of malnutrition showed a decreasing trend in underweight, an increasing trend for stunting and wasting, and overweight including a rising prevalence of dual burden of under-and overnutrition. The study indicates a high prevalence of undernutrition and a growing prevalence of overnutrition -the Asian paradox of the double burden of malnutrition in refugee children living in South Asia. The coexisting double burden of malnutrition among refugee children calls for comprehensive programs and policies for prevention and management of double burden of malnutrition.